Multibeam bathymetry processed data (EM 1002 echosounder entire dataset, MB-System data format) of RV MARIA S. MERIAN during cruise MSM24 - Paul Wintersteller; Janina Kammann; Anne Strack; Wolfram H Geissler (PANGAEA, 2021)
Processed multibeam echosounder (MBES) data recorded during RV MARIA S. MERIAN cruise MSM24 between 27.12.2012 and 21.01.2013 around Tristan da Cunha. The cruise MSM24 aimed to answer the question whether Tristan da Cunha classifies as a hot-spot with deep reaching asthenospheric anomalies and initiated the opening of the South Atlantic or whether Tristan da Cunha is a consequence of tectonic processes associated with more shallow anomalies. Another goal was to retrieve 26 ocean-bottom magnetotelluric stations (OBEM) and 22 broadband ocean-bottom seismometers (BBOBS) as well as two seismic and one magnetotelluric (MT) land stations from the uninhabited Nightingale Island. CI Citation: Paul Wintersteller (seafloor-imaging@marum.de) as responsible party for bathymetry raw data ingest and approval. The bathymetric post-processing was mainly conducted during RV MARIA S. MERIAN cruises MSM24 in 2013 around Tristan da Cunha. Final post-processing and creation of products were conducted by Janina Kammann (University Hamburg), Anne Strack (University Bremen / MARUM) and the Seafloor-Imaging & Mapping group of University Bremen / MARUM, responsible person: Paul Wintersteller (seafloor-imaging@marum.de). The open source software MB-system suite (Caress, D. W., and D. N. Chayes, MB-System: Mapping the Seafloor, https://www.mbari.org/products/research-software/mb-system, 2017) was utilized for this purpose. A tide correction was applied, based on the Oregon State University (OSU) tidal prediction software (OTPS) that is retrievable through MB-System. CTD measurements were taken during the cruise, and these were sufficient to represent the changes in sound velocity throughout the study area. Further roll, pitch and heave corrections were not applied for the MSM20-2 and MSM24 data. Bathymetric data has been manually cleaned for existing artefacts with mbeditviz. With mbmosaic one creates tables of the average amplitude and/or sidescan values as a function of the grazing angle with the seafloor that can be used by the program mbprocess to correct the sidescan or amplitude data for the variation with grazing angle. The mbprocess program applies changes to an extended raw data file annotaded with a "p" like "rawfilename"p.mbXX where XX stands for the MBES type, in case of EM122 it is mb59. The processed files allow further post-processing e.g. raytracing regarding sound velocity correction, gridding on different scales and merging of data on a hydroacoustic level, and are therefor the most valuable and sustainable product of a hydrographers workflow with MB-System. Description of the data source and the raw data itself can be found under: https://doi.org/10.1594/PANGAEA.898378 A composite grid (DTM) of the bathymetry of cruises MSM20-2 and MSM24 is published with the following DOI: https://doi.org/10.1594/PANGAEA.898303 Chief Scientist: Wolfram H. Geissler CR: https://doi.org/10.2312/cr_msm24 CSR: https://www2.bsh.de/aktdat/dod/fahrtergebnis/2012/20130046.htm ADCP: https://doi.org/10.1594/PANGAEA.823160